1682a 39 jobs. life, work and the many lessons of listening and talking along the way. (24th April 2018) - Nicholas, R
Abstract : Introduction: Life and work are personal, they evolve simultaneously. In my case, they have evolved through three careers—first as an environmental geologist, and then as an actor, writer and director in theatre and film. Ultimately, both careers merged into health and safety communications. But parallel to these three careers, I have had 39 jobs, spread across a variety of workplaces, co-workers, and bosses. Through all these jobs, I have learned crucial lessons, sometimes about what went wrong, but mostly about what went right. Methods: The jobs varied widely—working as a page in the United States Senate, canning peas for Green Giant, fighting forest fires for the U.S. Forest Service, writing environmental impact studies for geothermal energy, catering weddings. These and 34 other jobs provided a broad spectrum of work experiences and work environments. Results: The lessons learned varied widely, as well. For example, while working in the Senate, I was amazed how people could argue all day with completely opposite viewpoints, and then with respect and affection share dinner together. While canning peas, I learned what it feels like to be listened to, even though I was lowest in the hierarchy. In both catering and theatre, I saw how to correct someone's work while still maintaining the worker's privacy and dignity. And while writing environmental impact statements, I experienced how a 15 min conversation with my boss could change my life. Conclusions: These different experiences are anecdotal, they are personal. They certainly are not quantitative or prescriptive. But work, as in life, is both objective and personal. We limit ourselves when we forget to include our personal experiences at work, because those experiences are often what we remember most.